Supply Chain Analysis - Tang, Christopher S. (Springer, 2017)
SUPPLY CHAIN ANALYSIS: A Handbook on the Interaction of Information, System, and Optimization is a carefully developed work focused on the analysis of supply chain interaction issues in emerging markets and industry sectors. It is a leading-edge handbook that will emphasize where little work has been done and where the "rubber meets the road" — the supply chain process, information, and systems integration. These are pertinent issues facing practitioners and researchers in today’s business environment.